INVESTIGATION OF DIELECTRIC SPACED RESONANT MESH FILTER DESIGNS FOR PMIRR - Irwin, P; Ade, P; Calcutt, S; Taylor, F; Seeley, J; Hunneman, R; Walton, L (1993)
The fabrication of the filters for the two longest wave channels of the Pressure Modulator Infra-red Radiometer (PMIRR), launched in September 1992 on Mars Observer, was not possible using conventional multilayer dielectric techniques. Thus the extension of far-infrared/microwave mesh filter designs was investigated using a new dielectric spacing material. Test filters were designed and fabricated and, using their measured transmission spectra, a new model of the behaviour of resonant meshes in both air and dielectrics was developed. The low transmission of these filters in the end made them unsuitable for PMIRR but the model provides a useful design tool for future dielectric spaced filters providing a new, less absorbing dielectric can be found. © 1993.